TOPIC: "THE RICH CULTURAL HERITAGE OF THE UZBEK PEOPLE" (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article briefly discusses the ancient traditions, values, and the rich cultural heritage of the Uzbek people, which has a long and significant history.